Oral triiodothyronine for the prevention of thyroid hormone reduction in adult valvular cardiac surgery - Magalhães, A.P.A. (2006)
Treatment of non-thyroidal illness by intravenous triiodothyronine (T3) after cardiac surgery causes a disproportional elevation of hormone levels. The administration of oral T3, which has never been studied in this context, could cause physiological hormone levels. The aim of this study was to test oral T3 for the prevention of T3 reduction during the postoperative period of valvular cardiac surgery in adults. Eighteen patients who underwent cardiac surgery for valvular disease with invasive hemodynamic monitoring were randomly assigned to 2 groups: the T group received oral T3 (N = 8), 25 μg three times/day, initiated 24 h before surgery and maintained for 48 h and the NT group (N = 10) received placebo. Serum T3, thyroxine and thyrotropin were determined at baseline, 1 h before surgery, within 30 min of cardiopulmonary bypass and 6, 12, 24, and 48 h after removal of the aortic cross-clamp. Baseline T3 was similar in both groups (T: 119 ± 13; NT: 131 ± 9 ng/dL). Serum T3 increased during the first 24 h in the T group compared to the NT group (232 ± 18 vs 151 ± 13 ng/dL; P < 0.001). In the NT group, T3 was reduced by 24% (P = 0.007) 6 h after removal of the aortic cross-clamp, confirming the non-thyroidal illness syndrome. There were no differences in clinical or hemodynamic parameters between groups. Administration of oral T3 prevented its serum reduction after valvular cardiac surgery in adults, with normal serum levels for 48 h without disproportional elevations.